2012 IEEE International Conference on Computational Intelligence and Computing Research 2012
DOI: 10.1109/iccic.2012.6510277
|View full text |Cite
|
Sign up to set email alerts
|

Modeling self-Principal Component Analysis for age invariant face recognition

Abstract: Face recognition is a biometric approach which can extract the facial characteristics of a person without his/her cooperation. The face recognition system fails to identify a person after some years because of the age related variations shown on the face. The face recognition system should be able to handle such age related variations and recognise the person irrespective of his age. The aging variations on a face are seen in the form of wrinkles, shape changes etc. The process of aging is highly composite and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Meanwhile, recognizing the impact of age on gender classification performance, there is a suggestion to enhance the classification process by employing the Self-Principal Component Analysis (Self-PCA) method [12]. Self-PCA is a development of PCA that involves creating specific eigenfaces for each class to be identified, resulting in more accurate eigenfaces for each class [13]. The research demonstrated that the application of Self-PCA to facial images for gender classification, especially when considering the age factor, gives better performance than traditional PCA, using Euclidean distance measurement as the classifier.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, recognizing the impact of age on gender classification performance, there is a suggestion to enhance the classification process by employing the Self-Principal Component Analysis (Self-PCA) method [12]. Self-PCA is a development of PCA that involves creating specific eigenfaces for each class to be identified, resulting in more accurate eigenfaces for each class [13]. The research demonstrated that the application of Self-PCA to facial images for gender classification, especially when considering the age factor, gives better performance than traditional PCA, using Euclidean distance measurement as the classifier.…”
Section: Introductionmentioning
confidence: 99%
“…Locale around eyes is utilized as input feature highlight rather than whole face as it is progressively steady piece of face. J. S. Nayak and Nagarathna N. et al [7] proposed this self-PCA based face acknowledgment technique to think about maturing impacts by building subspace at individual dimension. Z. Li and U.…”
Section: Introductionmentioning
confidence: 99%
“…By arbitrary inspecting preparation set just as element space, different LDA-based classifiers are built and after that joined to create a strong choice by means of a combination rule[7].3.2.1 Densely sampled local feature descriptionThe entire face picture is partitioned into a lot of covering patches and after that chose neighborhood picture descriptors is connected to each fix. Removed highlights from these patches are connected together to frame a component vector with huge dimensionality for further investigation.…”
mentioning
confidence: 99%
See 2 more Smart Citations